1553 Non-Operative Management of Acute Appendicitis at A Major Trauma Centre – A Retrospective Case Series. (12th October 2021) - Chong, S J K; Kaur, M; Palmer, C; Jaunoo, S
Abstract: Aim: The recent CODA trial concluded that appendicitis patients with confirmed faecolith are at higher risk of appendicectomy and complications than those without faecolith. A retrospective case series of patients undergoing non-operative management of appendicitis at a major trauma centre was conducted to determine the success of non-operative management, defined as lack of operative management within 30 and 90 days of diagnosis, and the impact of presence of faecolith on outcomes. Method: All patients who received a working diagnosis of appendicitis over a 16-week period between March and June 2020 were identified and their electronic records interrogated for: preliminary and final diagnoses; imaging modality and result; operative or non-operative initial treatment strategy; final treatment strategy; and histopathology results where applicable. Patients who received an initial operative treatment strategy were excluded. Patients for whom appendicitis was not confirmed on either imaging or histopathology were excluded. Results: 24 patients received an initial non-operative treatment strategy and were eligible for inclusion. 15 patients (62.5%) underwent successful non-operative management. The remaining 9 patients (37.5%) required operative management within 30 days. Presence of faecolith was confirmed in 9 patients (37.5%). 3 patients (33%) with presence of faecolith required operative management, while 3 patients (25%) without presence of faecolith required operative management. 1 patient with confirmed faecolith developed a large intra-abdominal abscess while undergoing a non-operative treatment strategy and subsequently required right hemicolectomy. Conclusions: The majority of our eligible appendicitis patients were successfully managed non-operatively. Presence of faecolith in acute appendicitis is associated with increased risk of requiring operative management.